Science of problem solving in a historical context - Korn, Janos (Acta Europeana Systemica, 2020)
The generality of the ‘systemic or structural view’ of parts of the world is introduced. This leads to the generality of the ‘innate’ problem solving activity of problematic issues in the living sphere associated with survival or homeostasis, achievements of ambitions by chance or purpose and maintenance of isothermal operations. The anomaly of using predominantly qualitative, quantitative properties over the history of human intellectual endeavour for the development of empirical theories in preference of ‘systemic properties’, had they been available, is asserted. One- and two- place, declarative sentences of processed natural language acting as such properties, are suggested. Consideration of the notions of achievement and ambition leads to a ‘problem solving structure’ as the integral part of the ‘New science of systems’ called the ‘Science of problem solving’ or the ‘Science of the 21st century’. Accordingly, the problematic issues can be resolved and the anomaly to disappear. Aristotle’s four causes from the historical background of thought are compared with the problem-solving structure and the problem-solving function and place of conventional science of physics at the object level is discussed leading to a ‘scientific enterprise’. Integration of ancient and modern views has emerged. An example of application of ‘linguistic modelling’ to the problem-solving structure, is given.